In vitro inhibitory effects of ganoderic acid A on human liver cytochrome P450 enzymes - Shangchen Xu; Fengqing Zhang; Dali Chen; Keren Su; Li Zhang; Rui Jiang (Taylor & Francis Group, 2020)
Context Ganoderic acid A (GAA) is usually used to prevent cancers or other diseases, which make it likely to be used with other drugs metabolized by cytochromes P450. Objective This study investigates the effect of GAA on eight major cytochrome P450 isoforms in human liver microsomes. Material and method The effects of GAA (100 μM) on eight human liver CYP isoforms (i.e., 1A2, 3A4, 2A6, 2E1, 2D6, 2C9, 2C19, and 2C8) were investigated in vitro using human liver microsomes (HLMs) with specific substrates for the CYPs, and the enzyme kinetic parameters were calculated. Results The results showed that GAA inhibited the activity of CYP3A4, 2D6, and 2E1, but did not affect other isoforms. The inhibition of CYP3A4, 2D6, and 2E1 was concentration-dependent with IC50 values of 15.05, 21.83, and 28.35 μM, respectively. Additionally, GAA was not only a non-competitive inhibitor of CYP3A4, but also a competitive inhibitor of CYP2D6 and 2E1, with Ki values of 7.16, 10.07, and 13.45 μM. Meanwhile, the inhibition of CYP3A4 was time-dependent, with the KI/Kinact value of 7.91/0.048 μM/min. Discussion and conclusion The in vitro study indicated that GAA has the potential to result in drug-drug interactions with other drugs metabolized by CYP3A4, 2D6, and 2E1. Further clinical studies are needed for the identification of this interaction.